THE ROLE OF SCHOOLS IN INSTILLING ECOLITERACY TO BUILD STUDENTS' ENVIRONMENTAL AWARENESS: A CASE STUDY AT SDN SUSUKAN 07 PAGI - Salsabila Amalia Zulfa; Prima Mutia Sari (Universitas Majalengka, 2024)
This research focuses on urgency of environmental issues that require immediate attention, particularly through education. Public environmental awareness is still relatively low, necessitating the role of schools is needed in instilling ecoliteracy in students from an early age. Ecoliteracy is the ability to understand and maintain the environment well by recognizing the impact of one’s actions on nature and undertaking actions that help protect the environment. The purpose of this research is to determine the role and supporting as well as inhibiting factors of schools in instilling ecoliteracy to build students environmental awareness. This research was conducted at SDN Susukan 07 Pagi with class V participants. The research uses a qualitative approach with a case study design to gain in-depth understanding. Data collection techniques include interviews, observations, and documentation to gather informations from informants. Data analysis used the Miles and Huberman. The results of the research indicate that the school plays an important role in instilling ecoliteracy through the curriculum, extracurricular activities, and special environmental programs. At SDN Susukan 07 Pagi, ecoliteracy is implemented through the Merdeka curriculum, which integrates environmental materials into learning and school’s programs. This effort is supported by routine habituation activities such as work group ceremonies, the LISA (Lihat Sampah Ambil) program, spontaneous activities, role modeling from teachers and the principal, and good environmental conditioning. In conclusion, school activities effectively contribute to the instillation of ecoliteracy.